The Clinical Application and Prospect of Smart Prenatal Care and Postpartum Recovery. (6th October 2021) - Shu, Chang; Han, Shumei; Li, Linli; Xu, Peng; Bai, Yule
Abstract : Scientific and technological advancement has increased the requirement for modern medical systems, leading to smartphone-based intelligent prenatal care and postpartum recovery. This kind of prenatal care and postpartum recovery including a remote monitoring system for fetal heart monitoring, blood glucose, and weight overcomes the restrictions of time and space and provides all-round, convenient, rapid, and accurate services to the medical systems, doctors, and pregnant women. This paper reviews the current research on intelligent medical services for pregnant women, particularly for prenatal care and postpartum recovery.